Hyperinsulinism associated with GLUD1 mutation: allosteric regulation and functional characterization of p.G446V glutamate dehydrogenase - Karolina Luczkowska (Human Genomics, 2020)
Abstract Background Gain-of-function mutations in the GLUD1 gene, encoding for glutamate dehydrogenase (GDH), result in the hyperinsulinism/hyperammonemia HI/HA syndrome. HI/HA patients present with harmful hypoglycemia secondary to protein-induced HI and elevated plasma ammonia levels. These symptoms may be accompanied by seizures and mental retardation. GDH is a mitochondrial enzyme that catalyzes the oxidative deamination of glutamate to α-ketoglutarate, under allosteric regulations mediated by its inhibitor GTP and its activator ADP. The present study investigated the functional properties of the GDH-G446V variant (alias c.1496G > T, p.(Gly499Val) (NM_005271.4)) in patient-derived lymphoblastoid cells. Results The calculated energy barrier between the opened and closed state of the enzyme was 41% lower in GDH-G446V compared to wild-type GDH, pointing to altered allosteric regulation. Computational analysis indicated conformational changes of GDH-G446V in the antenna region that is crucial for allosteric regulators. Enzymatic activity measured in patient-derived lymphoblastoid cells showed impaired allosteric responses of GDH-G446V to both regulators GTP and ADP. In particular, as opposed to control lymphoblastoid cells, GDH-G446V cells were not responsive to GTP in the lower range of ADP concentrations. Assessment of the metabolic rate revealed higher mitochondrial respiration in response to GDH-dependent substrates in the GDH-G446V lymphoblastoid cells compared to control cells. This indicates a shift toward glutaminolysis for energy provision in cells carrying the GDH-G446V variant. Conclusions Substitution of the small amino acid glycine for the hydrophobic branched-chain valine altered the allosteric sensitivity to both inhibitory action of GTP and activation by ADP, rendering cells metabolically responsive to glutamine.